A Copper‐Catalyzed Variant of the Michaelis–Arbuzov Reaction. Issue 6 (10th April 2014) - Ballester, Jorge; Gatignol, Jérémie; Schmidt, Guntram; Alayrac, Carole; Gaumont, Annie‐Claude; Taillefer, Marc
Abstract As part of our studies on copper‐catalyzed arylation of nucleophiles, we report on Michaelis–Arbuzov reactions with a novel catalytic system, featuring a copper(I) salt as precatalyst without any additional ligand. This procedure is an interesting alternative to the use of expensive and toxic transition metals (nickel, palladium) traditionally used as catalysts in Michaelis–Arbuzov reactions. Our approach allows the synthesis from triethylphosphite, diethyl aryl phosphonite, and diaryl ethylphosphinite of various aryl phosphonates, aryl phosphinates, and aryl phosphine oxides, respectively. These families of compounds are essential owing to their respective importance in bioorganic and medical chemistry, their applicability as flame retardants, and their usability in coordination chemistry and catalysis.